Research trends e-module development in SINTA indexed Indonesian journal of biology education 2: A literature review - Ainanur Fauziyah Almaas; P. Paidi; M. Mualimin; Tatag Bagus Putra Prakarsa (University of Muhammadiyah Malang, 2025)
One of the educational resources that Indonesia has produced extensively is e-modules. It is still necessary to investigate and assess e-module development research. Analysis of e-module development publications in Indonesian biology education journals is the goal of this assessment of the literature. Only the JPBI (Jurnal Pendidikan Biologi Indonesia), BIOSFER (Journal of Biology Education), and Biolokus (all 2022–2024) editions of the SINTA 2 biology education publications are included in this study.